Product life cycle techniques: SMEs maintenance strategies - Endang Sungkawati; Niken Dwi Safitri; Adebayo Ola Afolaranmi (AMCA Journal of Community Development, 2023)
The food and beverage subsector of the industry is expanding. As the opportunities available to businesses grow, competition to maintain market share intensifies as the loss of a product diminishes its competitiveness. This leads to accumulating unsold products in the inventory even though increased sales volume could generate cash. Because the product cannot compete until the market reacts, it is not sold. Product demand rises in response to capacity constraints but must still be fulfilled. Increased sales are necessary to retain consumers during market expansion or contraction periods. By evaluating the literature, this study ascertains the most effective courses of action for two business scenarios. This study identifies product life cycle strategies supported by mixed marketing techniques in research indexed at least SINA 3, Scopus, or WOS between 2013 and 2023. According to the study, a business can flourish by offering discounts or special services to customers willing to wait while sales capacity increases.